A multicenter audit of the use of bronchoscopy during open and thoracoscopic repair of esophageal atresia with tracheoesophageal fistula. Issue 6 (12th June 2019) - Ahmad, Nargis S.; Dobby, Nadine; Walker, Eleanor; Sogbodjor, L. Amaki; Kelgeri, Nivedita; Pickard, Amelia; Burrows, Thomas D. R.; Nicholson, Katy E.; Green, Alice; Shepherd, Liz; Thornley, Helen; Wolfe Barry, Juliet A.; et al.
Abstract: Background: Esophageal atresia (EA) with tracheoesophageal fistula is usually repaired in the neonatal period. Preferential ventilation through the fistula can lead to gastric distension. Bronchoscopy has a role in defining the site and size of the fistula, and may be carried out by the surgeon or the anesthetist. The use of bronchoscopy varies across different institutions. Methods: This is a multicenter case note review of infants with EA with tracheoesophageal fistula who underwent surgery between January 2010 and December 2015. This retrospective audit aims primarily to document the use of bronchoscopy during open and thoracoscopic repair at a selection of United Kingdom centers. Respiratory complications, that is relating to airway management, the respiratory system, and difficulty with ventilation, at induction and during surgery,  are recorded. The range of techniques for anesthesia and analgesia in these centers is noted. Results: Bronchoscopy was carried out in 52% of cases. The incidence of respiratory complications was 7% at induction and 21% during surgery. Thoracoscopic repair usually took longer. One center used high‐frequency oscillatory ventilation, on an elective basis during thoracoscopic repair, to facilitate surgical access and address concerns about hypoxemia and hypercarbia. Conclusion: The use of bronchoscopy varies considerably between institutions. Infants undergoing tracheoesophageal fistula repair are at risk of perioperative respiratory morbidity. The advent of thoracoscopic repair has introduced further variation.